2019
DOI: 10.15381/rivep.v30i1.15679
|View full text |Cite
|
Sign up to set email alerts
|

Calidad de leche acopiada de pequeñas ganaderías de Cotopaxi, Ecuador

Abstract: Se analizó la calidad composicional, fisicoquímica e higiénica de la leche cruda acopiada en dos empresas procesadoras de lácteos en Cotopaxi, Ecuador, y se comparó con las normativas ecuatorianas. Se seleccionaron 10 proveedores por empresa para un total de 210 muestras por empresa colectadas en 21 días consecutivos. La calidad composicional (grasa) se midió con base a la norma INEN 0012, para la calidad fisicoquímico se utilizaron los métodos de análisis de las normas INEN 0009, INEN 0011, INEN 0013, CONVENI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 6 publications
0
5
0
9
Order By: Relevance
“…As for the results of the model, it can be observed that the average effect size of the bacterial count in graph A, represented by a rhombus, is 13.84, which is equivalent to (Exp 13.84 ), that is, 1,024,791.77 CFU/mL. Therefore, the estimated global mean and several studies are within the maximum allowed by NTE INEN 9 (≤1,500,000.00 UFC/mL); there are several studies that present bacterial counts much higher than this allowed maximum, as in the case of [ 23 , 26 ].…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…As for the results of the model, it can be observed that the average effect size of the bacterial count in graph A, represented by a rhombus, is 13.84, which is equivalent to (Exp 13.84 ), that is, 1,024,791.77 CFU/mL. Therefore, the estimated global mean and several studies are within the maximum allowed by NTE INEN 9 (≤1,500,000.00 UFC/mL); there are several studies that present bacterial counts much higher than this allowed maximum, as in the case of [ 23 , 26 ].…”
Section: Resultsmentioning
confidence: 93%
“…In the hydrogen potential (pH) parameter, the study of [ 24 ] has a mean above the stipulated value, while the studies of [ 18 , 23 , 26 , 43 , 44 , 57 ] are below the accepted minimum ( Figure 8 ). The pH helps to determine certain indicators of milk quality, such as conservation, since changes in this variable can modify the stability of the protein, causing unpleasant flavors in the milk [ 91 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…En el año 2018 las regiones Sierra Norte, Sierra Central y Amazonía presentaron valores < 400 × 10 3 células/mL y la región de la Costa presentó un valor mayor a 500 × 10 3 células/mL. En una investigación realizada en 7 provincias del Ecuador el 90 % de los productores manifestaron conocer la importancia de realizar la limpieza de ubres previo el ordeño y el secado pero solo el 65 % de los encuestados aplicaban una prueba de rutina para control de mastitis (Bonifaz y Requelme, 2011;Guevara-Freire y col., 2019). Por lo anteriormente señalado, era necesario definir las condiciones de manejo, producción y nutrición del ganado para el cumplimiento del RPCL en el Ecuador.…”
Section: Evolución De La Calidad Sanitaria E Higiénica 321 Contaje De Células Somáticasunclassified
“…En Ecuador, los estudios sobre la microbiología de la leche cruda bovina se han enfocado principalmente en la evaluación de los indicadores de calidad sanitaria, la búsqueda de ciertas bacterias patógenas, así como la evaluación de los aspectos relacionados con las regulaciones sanitarias y económicas (Arguelles et al, 2015;Chuquín Yépez et al, 2016;Chimborazo Ashqui, 2020;Contero et al, 2021;Guevara-Freire et al, 2019;Ramírez Robles y Lluman Marcatoma, 2020;Requelme y Bonifaz, 2012).…”
Section: Introductionunclassified